Crusading in Livonia and Byzantine Romania Considered in a Comparative Review. Key Issues and Historiographical Notes - Ivanov, Ivelin A. (Studia Ceranea, 2021)
The article focuses on a topic that so far has not been studied in a comparative approach. The author addresses some basic problems of the comparative research, focusing on the general and the specific causes, the course, and the consequences of the crusading actions in the lands of Livonia and Estonia – in the northeast, and Romania – in the southeast. Reconsidering the already established models and theses in historical research on the Baltic campaigns, on the one hand, and the Third, the Fourth, and the Fifth Crusades, on the other, the author formulates some guidelines and approaches for a comparative study on crusading ‘on the edges’ in the late 12th – the early 13th centuries. The article analyzes several factors including the role of geographical and climatic conditions, the demographic expansion, the papal policy, the commercial maritime activity, and the role of the Knightly orders in the crusading campaigns under review. Furthermore, the author explores the political and social background of the crusading campaigns under question and the different models of interaction between the colonization stratum and the local population in Livonia and the Latin Empire in Constantinople.